Risk and protective factors for intimate partner violence against women: Systematic review and meta-analyses of prospective-longitudinal studies - Yakubovich, A; Stöckl, H; Murray, J; Melendez-Torres, GJ; Steinert, J; Glavin, C; Humphreys, DK (American Public Health Association, 2018)
Background. The estimated lifetime prevalence of physical and/or sexual intimate partner violence (IPV) is 30% among women worldwide. Understanding risk and protective factors is essential for designing effective prevention strategies. Objective. To quantify the associations between prospective-longitudinal risk and protective factors and IPV and identify evidence gaps. Search methods. Systematic searches were conducted in 16 databases including MEDLINE and PsycINFO from inception to June 2016. The study protocol is registered with PROSPERO (CRD42016039213). Selection criteria. Published and unpublished studies available in English that prospectively analyzed any risk or protective factor(s) for self-reported IPV victimization among women, controlling for at least one other variable, were included. Data collection and analysis. Three reviewers were involved in study screening. Estimates of association and study characteristics were extracted from each study by one reviewer, with two reviewers independently checking a random subset of extractions. Study quality was assessed using the Cambridge Quality Checklists. When studies investigated the same risk or protective factor using similar measures, pooled odds ratios were computed using random-effects meta-analyses. Heterogeneity was indicated by I2 and τ2. All estimates of association, including those not meta-analyzed, were synthesized using harvest plots to illustrate evidence gaps and trends towards negative or positive associations. Main results. Of 18 608 studies identified, 60 were included and 35 meta-analyzed. Most studies were USA-based. The strongest evidence for modifiable risk factors for IPV against women were: unplanned pregnancy (OR = 1.66 [95% CI = 1.20, 1.31]) and having parents with less than a high school education (OR = 1.55 [95% CI = 1.10, 2.17]). Being older (OR = 0.96 [95% CI = 0.93, 0.98]) or married (OR = 0.93 [95% CI 0.87, 0.99]) were protective. Conclusions. This is the first systematic, meta-analytic review of all risk and protective factors for IPV against women without location, time, or publication restrictions. Unplanned pregnancy and having parents with less than a high school education, which may indicate lower socioeconomic status, were shown to be risk factors and being older or unmarried were protective. However, no prospective-longitudinal study investigated the associations between IPV against women and any community or structural factor outside the USA and more studies investigated risk factors related to women as opposed to their partners. Public health implications. This review highlights that prospective evidence for perpetrator- and context-related risk and protective factors for women’s experiences of IPV outside of the USA is lacking and urgently needed to inform global policy recommendations. The current evidence base of prospective studies suggests that, at least in the USA, education and sexual health interventions may be effective targets for preventing IPV against women, with young, unmarried women at greatest risk.